Pengembangan Sistem Informasi Kredit Usaha Rakyat Di PT. BPR Nusamba Tanjungsari - Muhamad Sandi Sudrajat; Jajat Sudrajat (STMIK Mardira Indonesia, Bandung, 2014)
People's Business Credit Application System Development in PT. BPR Nusamba Tanjungsari, its data processing still make use of Microsoft Excel or semi EDP (Electronic Data Processing) and not available file reports on a running system. The author also tries to make a credit application system using Delphi7 programming language that can generate a report file. The examines the system uses descriptive method and develop the waterfall method. The credit information system maybe one solution that can be used to facilitate the submission of the data processing system of credit reports credit transaction becomes easier, because the available facilities in this program directly print files to media reports the paper.Credit information system is built using Borland Delphi7 to make the main interface and Microsoft Accessas its database. This program allows the user to input the data, edit data, delete data, data retrieval, and data printing to paper media. The data entered in the form of customer data, the data requirements of credit and credit data. While the resulting output of this applicationin the form of credit data reports and reports of customer data. Keywords: credit application system